O significado da assistência pré-natal para gestantes atendidas em Unidade Básica de Saúde no Município de Maringá - PR - Ortigara, Elisangela Panosso de Freitas (2010)
The thematic Women's Health has been the focus of discussion increasingly present in the area of health research. In this sense, research on prenatal care are required to collaborate with this reality and the appropriateness of care provided to pregnant women in public health. Including the woman, user of a pre-natal system, in these studies is also respectable, since these individuals can contribute positively with their experience and opinion to improve care. This study aimed to understand the meaning of prenatal care for pregnant women enrolled in Basic Health Unit in Maringá - PR. Data collection occurred from November 2009 to February 2010 in the Basic Health Unit of Maringá, in which 44 women participated voluntarily. Information was gathered through interviews with central question taking into account the opinion of the women interviewed. Data analysis was done by the technique of collective subject discourse using the software Qualiquantisoft. The speeches drew to Central Ideas and anchors alike that express the meaning of prenatal care for pregnant women, and it was identified that pregnant women recognize their relevance to the health of mother and child, as well as the importance of having a monitoring by a health professional in this period, beyond criticism and praise about the care received. Negative aspects that lead women not to indicate the pre-natal is the lack of attention, lack of physicians and the need to stand in lines to receive assistance, and as positive aspects referring to the care received, the institution's phisician, the immediate attendance, the Unified Health System itself, good service and to live near Unit. Users advise dialogue and orientation on prenatal consultations, the importance of groups of pregnant women, the need for health professionals to attend prenatal care, the relevance of examinations and consultations. We conclude that understanding the meaning of prenatal care by the point of view of pregnant women allows to direct the way how the health care team should work together with these women during pregnancy. Much of what women expect from a quality prenatal care has more to do with the bond between client and professional, with attention and care, than with great technologies. The users' suggestions about the prenatal system allow to know what their real needs are, and thus, adequate the health service, where possible, to attend such events.